2016
DOI: 10.5698/1535-7511-16.3.187
|View full text |Cite
|
Sign up to set email alerts
|

2014 Epilepsy Benchmarks Area II: Prevent Epilepsy and Its Progression

Abstract: The prevention of epilepsy and its progression after initial diagnosis represents one of the most challenging goals of epilepsy research (1). Although epilepsy diagnoses lack a formal component of disease stage, anecdotal clinical observation suggests that individual patients usually fall into one of at least three types of presentation: an easily treated type that is responsive to the first or second antiseizure medications tried, a relapsing/ remitting type in which seizure control is intermittent, and a dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…• Registries of preclinical studies (eg, https://www.precl inica ltria ls.eu) The need for individualized or precision medicine approaches has been discussed for both genetic and nongenetic etiology epilepsies, considering the vast interactions and complexity of molecular, cellular, signaling, and network interactions and the age-, sex-, and timing-dependent effects of various treatments. [137][138][139][140][141] The preclinical WG emphasized the need to improve the infrastructure to allow precision medicine approaches for epilepsies, of both genetic and nongenetic etiologies, but also help optimize their translation into the clinics. Such infrastructure may include repositories of data and specimens to enable validation and translation of preclinical discoveries to the clinics, tools, and biomarkers to help identify target populations, deliver prognosis, and optimize treatment delivery decisions, but also research toward novel treatment delivery approaches targeting specific genes, cells, and circuits, at discreet time windows to minimize adverse effects.…”
Section: Challenges/gapsmentioning
confidence: 99%
See 1 more Smart Citation
“…• Registries of preclinical studies (eg, https://www.precl inica ltria ls.eu) The need for individualized or precision medicine approaches has been discussed for both genetic and nongenetic etiology epilepsies, considering the vast interactions and complexity of molecular, cellular, signaling, and network interactions and the age-, sex-, and timing-dependent effects of various treatments. [137][138][139][140][141] The preclinical WG emphasized the need to improve the infrastructure to allow precision medicine approaches for epilepsies, of both genetic and nongenetic etiologies, but also help optimize their translation into the clinics. Such infrastructure may include repositories of data and specimens to enable validation and translation of preclinical discoveries to the clinics, tools, and biomarkers to help identify target populations, deliver prognosis, and optimize treatment delivery decisions, but also research toward novel treatment delivery approaches targeting specific genes, cells, and circuits, at discreet time windows to minimize adverse effects.…”
Section: Challenges/gapsmentioning
confidence: 99%
“…The need for individualized or precision medicine approaches has been discussed for both genetic and nongenetic etiology epilepsies, considering the vast interactions and complexity of molecular, cellular, signaling, and network interactions and the age‐, sex‐, and timing‐dependent effects of various treatments 137‐141 . The preclinical WG emphasized the need to improve the infrastructure to allow precision medicine approaches for epilepsies, of both genetic and nongenetic etiologies, but also help optimize their translation into the clinics.…”
Section: Opportunities Challenges and The Path Forwardmentioning
confidence: 99%
“…Furthermore, in some other clinical studies, the role of proinflammatory cytokines as potential biomarkers of epilepsy severity has been suggested [ 42 45 ]. Therefore, the American Epilepsy Society (AES) and the National Institute of Neurological Disorders and Stroke (NINDS) identified IL-1β as a potential biomarker of epilepsy [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to epilepsy being the direct consequence of pathogenic variants in genes encoding proteins in epilepsy disorders, such as in glucose transporter type 1 deficiency syndromes, 2 it has been shown that maladaptive changes in metabolism contribute to epilepsy development. 3 Conversely, metabolic therapeutic approaches, such as the ketogenic diet (KD), have been shown (1) to influence the epigenome and (2) to prevent epileptogenesis. [4][5][6][7][8] The KD suppresses seizures in some patients, reflecting the antiepileptic effects of specific metabolic changes.…”
Section: Metabolic Mechanismsmentioning
confidence: 99%